Physical properties of buckwheat (Fagopyrum esculentum Moench) grains during convective drying - Wellytton D. Quequeto; Valdiney C. Siqueira; Vanderleia Schoeninger; Elton A. S. Martins; Eder P. Isquierdo; Fernanda P. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Buckwheat is a prominent crop in present-day agriculture due to its nutraceutical properties; however, information on this crop regarding the post-harvest process is scarce, as well as the characterization of its physical properties and such information is essential for the development and improvement of machinery used in post-harvest processes. Thus, the objective of this study was to determine the volumetric shrinkage, porosity, bulk density and true density of buckwheat grains throughout the drying process, as well as to fit mathematical models to the experimental values of true and bulk volumetric shrinkages. Buckwheat grains of the cultivar IPR 91 - Baili with an initial moisture content of 0.250 (decimal, dry basis.) were used. The samples used to determine the physical properties were subjected to oven drying with forced air circulation stabilized at 40 ± 1 °C. The mass of the samples was periodically weighed, so that when the product reached predetermined values of moisture content, the samples were removed and their physical properties were determined. It is concluded that the reduction in moisture content during drying causes increase in bulk density, true density and porosity. The reduction of the moisture content influences bulk volumetric shrinkage and true volumetric shrinkage of the grains, causing reductions in their values of approximately 14.47 and 14.70%, respectively, and a linear model can represent both variables satisfactorily.